The significance of climate in the pollinator dynamics of a tropical agroforestry system - Arnold, S.E.J. (2018)
Even though many globally important tropical agroforestry crops are partially or completely dependent on insect pollination, the conditions influencing pollinator abundance in these systems are often incompletely understood. This is particularly the case for cocoa midges (Diptera: Ceratopogonidae), which are essential for cocoa pollination and thus yield, but agro-ecological management frequently neglects them. We report the first assessment of cocoa midge population dynamics from two Caribbean countries across a full year, and relate this to seasonal climate variables. We used static suction traps along transects to sample insects monthly, from six cocoa farms across three Caribbean islands, with a particular focus on known pollinators of cocoa. A total of over 87,000 insects were captured, including more than 1800 cocoa midges. Midges were present in all months of the survey and on all sites, but typically comprised less than 2% of the total insects caught. At least twelve different species of cocoa midges were identified from this survey. The previous month's rainfall positively predicted cocoa midge absolute abundance and further analysis also revealed a relationship between rainfall and relative midge abundance. In particular, during drought periods, midge numbers were very low, consistent with their larval ecology. Humidity and mean daily maximum and minimum temperatures did not relate to midge abundance. Rainfall negatively influenced the Shannon-Weaver index. The findings highlight the possible threat of droughts to cocoa pollination services and the importance of proactive farm management to support them.